Crop lodging: its causes and management for sustainable crop production - Jiger, Dinesh; Dhar, Shiva; Kaur, Ramanjit (Indian Farming, 2018)
In cereals, considerable loss in yield and quality occurs due tolodging. Crops are more susceptible to lodging at the later stages of crop maturity. Losses in yields due to lodging vary from crop to crop and the loss is greatest in crops like wheat, rice, barley and millets. Losses will be greatest under high input and mechanized agriculture. All highyielding factors like varieties, fertilizers, population and irrigation affect the lodging. Careful management of the factors like selection of resistant genotypes, following raised bed cultivation, proper application of nitrogen (N) and potassium (K) fertilizers, irrigation at optimum time and quantity and application of plantgrowth regulators may undeniably reduce the lodging and improve the yield and quality of crops.